Indirect searches of dark matter in dwarf galaxies with the Southern Wide-field Gamma-ray Observatory - Andrade, Micael Jonathan Duarte (2023)
Currently, one of the most profound mysteries in physics is the nature of dark matter particles. Its existence is inferred through the gravitational effects it has on visible matter, but it has not yet been directly or indirectly observed. Among the methods for searching for dark matter, indirect detection involves looking for the Standard Model particles produced by the decay or self-annihilation of dark matter particles. Within the mass range of GeV to TeV for the dark matter particle, this type of search can be conducted through the detection of gamma rays in dark matter dominated systems. Dwarf galaxies are excellent targets for this type of observation as they are dominated by dark matter and are relatively close to Earth, when compared to other possible targets. In this dissertation, the detectability of dark matter annihilation or decay signals from dwarf galaxies is predicted for The Southern Wide-field Gamma-ray Observatory (SWGO), a future observatory that will be built in South America. This instrument will be able to study many important dark matter dwarfs targets in the Southern Hemisphere and it is shown that the combined observation of all targets would be able to provide competitive limits in the mass range between GeV to PeV.